Pengembangan Model Latihan Speed, Agility, Quickness (SAQ) Untuk Meningkatkan Kelincahan Atlet Tenis Yunior - syati, gita laras; Nasuka, Nasuka (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
The aim of this research is to develop a SAQ (Speed, Agility,Quickness ) training model, analyzing the effect of developing a training model to increase agility . This research uses the R&D (research and development ) method. The quantitative data analysis technique in this research uses descriptive statistics using a Likert scale . , Analysis of Variance (Anova) at the significant level (0.005). The population in this study was the Pantai Timur Tennis Club (10 Athletes) for small group trials and the Volta Tennis Club (22 Athletes) for large group trials. The results of the research show that: the results of the field tennis validator with a percentage of 81% description "Valid", the results of the material validator with a percentage of 81% description "Valid", the results of small group trials with a percentage of 87% description "Valid", and the results of group trials large with a percentage of 87% of “Valid” descriptions. For significant test results on increasing Agility, the research conclusion is declared significant if the calculated t value > t table and the sig value is smaller than 0.05 (Sig < 0.05). Keyword : Training models, Speed, Agility, Quickness, Tennis.